Methodologies and Models for Integration of Medical Curriculum for Effective Teaching and Learning: A Theoretical Review - Kasarla, Rajeshwar Reddy; Verma, Aishwarya; Pathak, Laxmi (Journal of Universal College of Medical Sciences, 2022)
There is a famous saying that, ‘Knowledge that is learnt in isolation is rapidly forgotten’. The dictionary meaning of integration is “to make entire”. Integration is defined as the organization of teaching matter to interrelate or unify the subjects which are frequently taught in separate academic courses or departments. Integrated curriculum seeks to break down the barriers between the subject areas i.e. basic and clinical sciences, in order to promote acquisition, retention, and progressive development of knowledge and skills, and facilitate applications of principles and concepts to understand problems and develop new solutions. To learn is to connect thoughts and ideas. If there is no connection, there is no learning. Integration views learning and teaching in a holistic way and reflects the real world, which is interactive. Disconnection breeds apathy while integration thrives on connections. An integrated curriculum helps raising students who will be able to apply their knowledge to their work and personal development. Integrating curriculum is a complex process. It can occur at different rates and some subjects are integrated more easily than others. This article reviews and discusses the comparison and commonalities of two most prominent methodologies/models of integration by Robin Fogarty and Ronald Harden.